ANALISIS PENYELESAIAN PEMBIAYAAN BERMASALAH DI UNIT USAHA BANK KALTIMTARA SYARIAH KC SAMARINDA - Linda, Norma; Iswadi, Muhammad; Hasbi, Muhammad (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2024)
Non Performing Financing is a condition where financing activities meet the agreed conditions for repayment of the financing, resulting in a delay, so action is required by the bank. This research aims to find out the level of problematic financing, what are the factors of problematic financing and how to resolve problematic financing in the Bank Kaltimtara Syariah Business Unit KC Samarinda.This research uses descriptive qualitative research, which is a research method that emphasizes the aspect of in-depth understanding of a problem so that the research can be of high quality, so the data collected must be complete in the form of primary data and secondary data. Data collection techniques in this research used observation, interview and documentation techniques. And the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions.The results of this research show that the level of financing at Bank Kaltimtara Syariah for problem financing is classified as healthy. Because it has decreased in the past three years, this is reflected in the financial statements, namely in 2020 it was 2.96%, in 2021 it was 2.78% and in 2022 it was 0 .78%. There is 1 factor that causes problematic financing at Bank Kaltimtara Syariah KC Samarinda, namely external factors. Problematic financing can occur but not too much because those who apply for financing are customers who choose consumer products. Meanwhile, for productive products, problematic financing occurs in During the pandemic, customers experienced unexpected events, namely a decrease in turnover. Resolving financing problems in productive financing products by holding discussions to obtain information about problems in the customer's business. Then the bank also held a Restructuring Option. Meanwhile, for consumer financing products, the solution is for the party to give a warning letter or block salaries and take over to another bank